Nilai Budaya Tanam Padi sebagai Daya Tarik Wisata - Didin Syarifuddin (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
West Java is the centre of Indonesian rice production, which contributes 16 per cent of the national rice production. However, these advantages have not contributed to the growing awareness of the younger generation to preserve the rice planting culture. On the basis of these problems, the purpose of this study is to explain how the cultural value of rice planting with the tourist attraction of the Cikondang Traditional Village community. The research method used is a qualitative method, through in-depth interviews and groups, with data reduction analysis and data presentation. The results showed that the rice planting procession was loaded with cultural values and had a tourist attraction. This value is reflected in the value of human nature, the nature of human relations with the surrounding environment, the essence of human position in space and time, the essence of human relations with work and charity and the nature of human relations with other humans. Meanwhile, the attraction of the tour is reflected in the uniqueness, attractiveness, rarity, authenticity, cleanliness and safety